Cancer and Pregnancy in the Post-Roe v. Wade Era: A Comprehensive Review - Ganguly Arup; Narmala Shravan (Current Oncology, 2023)
Cancer during pregnancy, affecting 1 in 1000 pregnancies, is rising in incidence due to delayed childbearing and improved detection. Common types include breast cancer, melanoma and cervical cancer and Hodgkin’s Lymphoma. There are several physiological changes that occur during pregnancy that make its management a challenge to clinicians. Managing it requires multidisciplinary approaches and cautious test interpretation due to overlapping symptoms. To minimize fetal radiation exposure, non-ionizing imaging is preferred, and the interpretation of tumor markers is challenging due to inflammation and pregnancy effects. In terms of treatment, chemotherapy is avoided in the first trimester but may be considered later. Immunotherapy’s safety is under investigation, and surgery depends on gestational age and cancer type. Ethical and legal concerns are growing, especially with changes in U.S. abortion laws. Access to abortion for medical reasons is vital for pregnant cancer patients needing urgent treatment. Maternal outcomes may depend on the type of cancer as well as chemotherapy received but, in general, they are similar to the non-pregnant population. Fetal outcomes are usually the same as the general population with treatment exposure from the second trimester onwards. Fertility preservation may be an important component of the treatment discussion depending on the patient’s wishes, age and type of treatment. This article addresses the complicated nature of a diagnosis of cancer in pregnancy, touching upon the known medical literature as well as the ethical–legal implications of such a diagnosis, whose importance has increased in the light of recent judicial developments.